2020
DOI: 10.1136/bmjdrc-2020-001402
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation profile in infants born small-for-gestational-age: association with markers of adiposity and insulin resistance from birth to age 24 months

Abstract: IntroductionPrenatal growth restraint followed by rapid postnatal weight gain increases lifelong diabetes risk. Epigenetic dysregulation in critical windows could exert long-term effects on metabolism and confer such risk.Research design and methodsWe conducted a genome-wide DNA methylation profiling in peripheral blood from infants born appropriate-for-gestational-age (AGA, n=30) or small-for-gestational-age (SGA, n=21, with postnatal catch-up) at age 12 months, to identify new genes that may predispose to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…The exact mechanism of the association of SGA with diabetes and cardiovascular disease is unknown, although various hypotheses have been proposed, such as a mis-match between the prenatal and postnatal environments. Fetal nutrition may be poor whereas neonatal nutrition may be better, resulting in low birth weight and subsequent rapid weight gain, which may affect pancreatic function ( 38 ), possibly through epigenetic changes in DNA methylation ( 39 ). Children born SGA are at risk for rapid development of decreased insulin sensitivity compared with those born appropriate for gestational age (AGA), particularly in those who have catch-up growth ( 40 43 ).…”
Section: Effect Of Being Born Sga On Growth and Metabolism In Adolescence And Young Adulthoodmentioning
confidence: 99%
“…The exact mechanism of the association of SGA with diabetes and cardiovascular disease is unknown, although various hypotheses have been proposed, such as a mis-match between the prenatal and postnatal environments. Fetal nutrition may be poor whereas neonatal nutrition may be better, resulting in low birth weight and subsequent rapid weight gain, which may affect pancreatic function ( 38 ), possibly through epigenetic changes in DNA methylation ( 39 ). Children born SGA are at risk for rapid development of decreased insulin sensitivity compared with those born appropriate for gestational age (AGA), particularly in those who have catch-up growth ( 40 43 ).…”
Section: Effect Of Being Born Sga On Growth and Metabolism In Adolescence And Young Adulthoodmentioning
confidence: 99%
“…We recently reported that GPR120 -a key regulator of adipogenesis-is hypermethylated in cord blood of SGA newborns and also in peripheral blood at age 1 year and is associated with lower fat mass at the age of 1 and 2 years. 12,13 Thus, it is tempting to speculate that the increased levels of DBI in SGA infants could be a compensatory mechanism to promote lipogenesis and adipocyte differentiation. Along these lines, it has been reported that DBI knock-down inhibits the ability of murine 3T3-L1 pre-adipocytes to undergo differentiation and to induce key adipogenic transcription factors like PPARγ.…”
Section: Discussionmentioning
confidence: 99%
“…The study cohort was composed of 103 infants [70 AGA (49% girls) and 33 SGA (48% girls)] who were recruited into two previous longitudinal, prospective studies (Supplemental Figure S1, flow chart). Study 1 assessed body composition and endocrine-metabolic variables of SGA vs AGA-breastfed infants in the first 2 years of life 11 ; study 2 assessed DNA methylation of SGA vs AGA infants in placenta and cord blood, as well as at age 12 months, together with endocrinemetabolic and body composition markers 12,13 ; in a subpopulation of infants enrolled in both study 1 and study 2, growth-anddifferentiation factor-15 had also been measured longitudinally. 14 The present study focused on DBI measurement, with the following inclusion criteria: (1) uncomplicated, singleton pregnancy; (2) Caucasian origin; (3) term birth (37-42 weeks) at Hospital Sant Joan de Déu, Barcelona; birth weight between 2.9 and 3.8 kg for AGA (range À 1.1 and + 1.1 SD) and between 1.9 and 2.6 kg for SGA (below À2 SD); (4) exclusive breastfeeding or formula feeding in the first 4 months; (5) spontaneous catch-up in weight and length in SGA subjects, defined as weight and length Z-score > À2.0 by age 1 year 15 ;…”
Section: Study Populationmentioning
confidence: 99%
“…Current research to establish better ways to determine which infants are pathologically small might help us to prevent perinatal morbidity and mortality [ 22 ]. Recently, genes in SGA infants, which are related to B cell development, metabolism, and obesity, were found to be hypomethylated compared to those in non-SGA infants [ 23 ]. Thus, DNA methylation profiles may prove to be a useful diagnostic tool if epigenetic changes are indeed the key mechanism underlying DoHAD and the pathogenesis behind SGA.…”
Section: Physiologic Mechanisms Linking Low Birth Weight and Adult Diseasementioning
confidence: 99%